Driving Influences of the Doppler Flash Observed by SuperDARN HF Radars in Response to Solar Flares. Issue 6 (3rd June 2022) - Chakraborty, S.; Qian, L.; Baker, J. B. H.; Ruohoniemi, J. M.; Kuyeng, K.; Mclnerney, J. M.
Abstract: Sudden enhancement in high‐frequency absorption is a well‐known impact of solar flare‐driven Short‐Wave Fadeout (SWF). Less understood, is a perturbation of the radio wave frequency as it traverses the ionosphere in the early stages of SWF, also known as the Doppler flash. Investigations have suggested two possible sources that might contribute to it's manifestation: first, enhancements of plasma density in the D‐and lower E‐regions; second, the lowering of the F‐region reflection point. Our recent work investigated a solar flare event using first principles modeling and Super Dual Auroral Radar Network (SuperDARN) HF radar observations and found that change in the F‐region refractive index is the primary driver of the Doppler flash. This study analyzes multiple solar flare events observed across different SuperDARN HF radars to determine how flare characteristics, properties of the traveling radio wave, and geophysical conditions impact the Doppler flash. In addition, we use incoherent scatter radar data and first‐principles modeling to investigate physical mechanisms that drive the lowering of the F‐region reflection points. We found, (a) on average, the change in E‐ and F‐region refractive index is the primary driver of the Doppler flash, (b) solar zenith angle, ray's elevation angle, operating frequency, and location of the solar flare on the solar disk can alter the ionospheric regions of maximum contribution to the Doppler flash, (c) increased ionospheric Hall and Pedersen conductance causes a reduction of the daytime eastward electric field, and consequently reduces the vertical ion‐drift in the lower and middle latitude ionosphere, which results in lowering of the F‐region ray reflection point. Plain Language Summary: A sudden eruption of electromagnetic radiation from the sun, also known as a solar flare, alters the physical properties of the ionosphere, creating ionospheric perturbations, commonly referred to as a sudden ionospheric disturbance (SID). As a result of ionosphere perturbations due to a solar flare, the over the horizon radio channels on the dayside of the Earth can be disrupted, which is also known as shortwave fadeout. It is well known and understood that ionospheric radio waves are absorbed during a solar flare‐driven SID. In contrast, the initial Doppler frequency shift, also known as "Doppler flash", in the traveling radio wave is a recently discovered phenomenon that is not yet fully understood. The purpose of this paper is to advance our understanding of the initial impacts of solar flares on ionospheric properties using simulated data and observations from multiple events. Key Points: Changes in the E‐ and F‐region refractive index are the drivers of the Doppler flash Characteristics of the Doppler flash are affected by zenith angle, frequency, elevation angle, and flare location on the solar disk Lowering of the F‐region ray reflection height is driven by the flare‐enhanced E‐region Hall and Pedersen conductance